Communication barriers in caring for culturally diverse patients and the cultural competence of nursing staff - Charzyńska-Gula, Marianna; Zych-Kwaśnik, Katarzyna; Rożek, Grażyna; Szulich, Piotr; Sojda, Agnieszka; Tomczyk, Bogdan; Zielińska, Marta (Journal of Education, Health and Sport, 2024)
Introduction: The culturally different patient is still a new task for nursing staff. In order to realise competent and effective care for a patient from a different culture, the nurse must be able to recognise her own cultural filters, communication barriers, cultural differences, the sometimes different value system and its relevance to the patient's quality of life Objective of the study: The aim of this study is to illustrate the communication barriers in caring for a culturally different patient in a selected group of nursing staff and to contrast them with the cultural competences possessed by this group. Material and method: 127 nursing staff of one of the Podkarpackie hospitals were studied. A diagnostic survey with an author's survey questionnaire and the Polish version of the Cultural Competence Scale of Medical Personnel were used. Results: Individuals with higher cultural competence in behaviour were better able to cope with communication barriers in terms of language differences and non-verbal communication. Higher cultural competence in patient-centred communication was associated with better coping with barriers in terms of cultural differences and non-verbal communication. The higher the cultural competence in practice orientation, the lower the coping with excess emotions or information and the worse the coping with the patient's culture and values conflicting with the patient's own culture and value system. Those who scored higher on the self-assessment of cultural competence simultaneously coped better with barriers concerning language differences. Those who showed higher awareness and sensitivity with regard to cultural competence coped less well with emotional excess. Conclusions: Relatively good levels of problem solving related to communication barriers are not always accompanied by full cultural competence.